Method for manufacturing precursor sheet for recycled fuel cell separator
Patent Information
- Application Number
- JP2023140043
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-08-30
- Publication Date
- 2025-03-13
- Estimated Expiration
- 2043-08-30
AI Technical Summary
【0010】 本発明によれば、燃料電池セパレータ用前駆体の製造時に発生した不良品や、加工時の端材を再スラリー化して再び燃料電池セパレータ用前駆体に加工し直すことができるため、製造時のロスを削減することができる。
Smart Images

Figure 2025033963000001 
Figure 2025033963000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for making a precursor for a regenerative fuel cell separator. [Background technology]
[0002] The fuel cell separator serves to provide electrical conductivity to each unit cell, ensure passage of fuel and air (oxygen) supplied to the unit cells, and act as a boundary wall separating them. Generally, properties required for fuel cell separators include gas (hydrogen and oxygen) impermeability, electrical conductivity, mechanical strength, durability (heat resistance, water resistance, acid resistance), thin and lightweight, and formability.
[0003] A conventional method for producing such fuel cell separators is to heat and compress a sheet-like separator precursor. For example, Patent Document 1 discloses a fuel cell separator comprising a conductive base sheet, a dense layer containing first graphite particles having a predetermined bulk density and volume resistivity (conductivity), and a conductive layer containing second graphite particles having a predetermined bulk density and volume resistivity, the dense layer and the conductive layer being obtained by compression molding a precursor sheet for a fuel cell separator containing a resin. Patent document 2 discloses a fuel cell separator obtained by thermoforming a stampable sheet containing a conductive filler and a polymeric material in a molding machine equipped with a pair of dies engraved with the shape of a fuel cell separator.
[0004] Thus, although there have been many separator manufacturing techniques using sheet-shaped precursors, there has been no known means for easily reusing the sheet-shaped precursors in an aqueous solvent (by forming a slurry). For example, Patent Document 1 discloses that the above-mentioned conductive layer can be produced using a conductive layer-forming composition containing a water-soluble resin as a binder, graphite, and a resin. However, since the conductive layer is impregnated with a non-water-soluble resin liquid dissolved in a solvent, the non-water-soluble resin liquid coats the graphite and causes the graphite to adhere, making it difficult to re-dissolve it in an aqueous solvent or re-slurry it for reuse. Patent Document 2 also uses a stampable sheet manufactured by a paper-making method from a suspension containing a conductive filler and a polymer material. However, when the sheet is made, it is dried at high temperature and then pressed. This causes the polymer particles to adhere to each other and to the polymer material and the conductive filler, making it difficult to re-dissolve the sheet in an aqueous solvent or re-slurry it for reuse. Furthermore, none of the documents mentions anything about reusing the sheet-like precursor. Furthermore, separators obtained from conventional sheet-like precursors have the problem of poor electrical conductivity because insulating layers of water-insoluble resins are likely to form between the graphite particles on the surface and on the surface of the graphite particles.
[0005] Furthermore, Patent Document 3 discloses a coating composition for use in a current collector plate with a coating layer for a fuel cell, which contains a carbon material, a water-soluble resin binder, a water-dispersible resin particulate binder, and an aqueous liquid medium, and Patent Document 4 discloses a coating composition for use in a separator with a coating layer for a fuel cell, which contains a carbon material, a water-soluble resin binder, a water-dispersible resin particulate binder, and an aqueous liquid medium. However, the compositions of Patent Documents 3 and 4 are coating compositions for coating the surfaces of current collectors or separators, and are not precursor sheets for fuel cell separators. Furthermore, the above coating compositions are not only not formed into a sheet to be used as separator precursors, but also cannot be reused by redissolving in an aqueous solvent or reslurrying, since they form a water-resistant coating film after application and drying. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] Patent No. 7056796 [Patent Document 2] JP 2006-269313 A [Patent Document 3] JP 2016-183325 A [Patent Document 4] JP 2016-81717 A Summary of the Invention [Problem to be solved by the invention]
[0007] The present invention has been made in consideration of the above circumstances, and aims to provide a method for manufacturing a precursor for a regenerated fuel cell separator, which converts, for example, defective products generated during manufacturing or scraps generated during processing into reusable materials as precursors for fuel cell separators. [Means for solving the problem]
[0008] As a result of extensive research to achieve the above-mentioned object, the inventors discovered that a precursor for a fuel cell separator containing graphite particles and a water-soluble resin can be reslurried in an aqueous solvent, making it possible to easily reuse defective products generated during manufacturing and scraps generated during processing, and thus completed the present invention.
[0009] That is, the present invention provides 1. A method for producing a precursor for a regenerated fuel cell separator, comprising the steps of: mixing a precursor for a fuel cell separator, which precursor contains graphite particles and a water-soluble resin, with an aqueous solvent to prepare a slurry; and drying the slurry. 2. The method for producing a regenerated fuel cell separator precursor according to claim 1, wherein the fuel cell separator precursor contains a particulate or fibrous water-insoluble resin. 3. A method for producing a fuel cell separator, comprising a step of molding a precursor for a regenerated fuel cell separator obtained by the method for producing a precursor for a regenerated fuel cell separator according to 1 or 2. 4. The method for producing a fuel cell separator according to claim 3, wherein the molding step is a step of heat compression molding. to provide. Effect of the Invention
[0010] According to the present invention, defective products generated during the production of fuel cell separator precursors and scrap materials generated during processing can be reslurried and reprocessed into fuel cell separator precursors, thereby reducing losses during production. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] The present invention will be described in further detail below. The method for producing a precursor for a regenerated fuel cell separator (hereinafter abbreviated as "regenerated precursor") according to the present invention is characterized by comprising a step of mixing a precursor for a fuel cell separator (hereinafter abbreviated as "precursor") containing graphite particles and a water-soluble resin with an aqueous solvent to prepare a slurry, and a step of drying the prepared slurry.
[0012] [1] Graphite particles The graphite particles constituting the precursor used in the present invention are not particularly limited, and either natural graphite or artificial graphite may be used. The artificial graphite particles can be appropriately selected from those conventionally used in fuel cell separators, specific examples of which include artificial graphite obtained by calcining needle coke, artificial graphite obtained by calcining lump coke, and the like. On the other hand, the natural graphite particles may be appropriately selected from those conventionally used in fuel cell separators, specific examples of which include lump natural graphite and flake natural graphite. These graphite particles may be used alone or in combination of two or more kinds.
[0013] The shape of the graphite particles is not particularly limited, but from the viewpoint of electrical conductivity, a spherical or flaky shape is preferred. The average particle size of the graphite particles is not particularly limited, but in consideration of increasing the electrical conductivity, it is preferably 5 to 200 μm, more preferably 10 to 200 μm, even more preferably 10 to 100 μm, and even more preferably 10 to 50 μm. In the present invention, the average particle size is the median diameter (d 50 ) (hereinafter the same).
[0014] [2] Water-soluble resin The water-soluble resin preferably has dispersibility, viscosity increasing property, and adhesive property from the viewpoint of uniformly dispersing the graphite particles and the particulate or fibrous water-insoluble resin used as necessary and further reconstituting the precursor. In the present invention, "water-soluble" means that the resin is completely dissolved in water at 25°C at a concentration of at least 1% by mass. Specific examples of the water-soluble resin include aqueous resins such as acrylic resins, polyvinyl resins, polyether resins, polyurethane resins, polyester resins, polyolefin resins, polyamide resins, polyimide resins, polyallylamine resins, phenol resins, epoxy resins, phenoxy resins, urea resins, melamine resins, alkyd resins, formaldehyde resins, silicone resins, fluororesins, and polysaccharides such as carboxymethylcellulose, which may be used alone or in combination of two or more. Among these, acrylic resins, polyvinyl resins, polyether resins, and polysaccharides such as carboxymethylcellulose are preferred from the viewpoint of uniformly dispersing graphite particles and particulate or fibrous water-insoluble resins used as needed with a particularly small amount of addition, and regenerating them into precursors. These water-soluble resins are commercially available.
[0015] The content of the water-soluble resin in the precursor used in the present invention is not particularly limited as long as the precursor can be reslurried, but from the standpoint of ease of reslurrying the precursor and dispersibility of the slurry, the content is preferably 0.1 to 30.0 parts by mass, and more preferably 0.5 to 25.0 parts by mass, relative to 100 parts by mass of graphite particles, and furthermore from the standpoint of increasing the strength of the regenerated precursor, 1.0 to 25.0 parts by mass is even more preferable.
[0016] [3] Particulate or fibrous water-insoluble resin The precursor used in the present invention preferably contains a particulate or fibrous water-insoluble resin. This water-insoluble resin is not particularly limited as long as it is particulate or fibrous and does not dissolve in water, and may be a thermoplastic resin or a thermosetting resin. As the thermoplastic resin, a resin having a melting point or glass transition point of 100° C. or higher is preferred, since it has heat resistance that allows it to maintain a particulate or fibrous form during drying in producing the precursor. Specific examples thereof include polyethylene, polypropylene, polyphenylene sulfide, polytetrafluoroethylene, tetrafluoroethylene-ethylene copolymer, polychlorotrifluoroethylene, polyamide, polyetherketoneetherketoneketone, polyetherketone, liquid crystal polymer, polyimide, polyamideimide, polyphenylsulfone, polyetherimide and polysulfone, polybutylene terephthalate, polyethylene naphthalate, ABS resin, polycycloolefin and polyethersulfone, and derivatives thereof having a melting point of 100° C. or higher, polycarbonate, polystyrene and polyphenylene oxide, and derivatives thereof having a glass transition point of 100° C. or higher, which may be used alone or in combination of two or more. The upper limit of the melting point or glass transition point is not particularly limited, but from the viewpoint of productivity of the precursor and the fuel cell separator, it is preferable that it is 300° C. or lower.
[0017] The thermosetting resin can be appropriately selected from those that have been conventionally used as binder resins for carbon separators and the like. Specific examples thereof include phenolic resins, epoxy resins, furan resins, unsaturated polyester resins, urea resins, melamine resins, diallyl phthalate resins, bismaleimide resins, polycarbodiimide resins, silicone resins, vinyl ester resins, benzoxazine resins, etc., which may be used alone or in combination of two or more. Among these, epoxy resins and phenolic resins are preferred because of their excellent heat resistance and mechanical strength. These water-insoluble resins are commercially available.
[0018] The particle shape of the water-insoluble resin is not particularly limited and may be any shape such as spherical, scale-like, block-like, foil-like, plate-like, needle-like, amorphous, etc., but from the viewpoint of particle packing, a spherical shape is preferred. The average particle size of the water-insoluble resin is not particularly limited, but is preferably 1 to 150 μm from the viewpoints of increasing the packing properties of the particles and reducing the resistance of the resulting fuel cell separator.
[0019] When the precursor used in the present invention contains a particulate or fibrous water-insoluble resin, the content thereof is not particularly limited as long as the precursor can be reslurried. From the viewpoint of ease of reslurrying, the content is preferably 10.0 to 70.0 parts by mass, and more preferably 15.0 to 65.0 parts by mass, per 100 parts by mass of the graphite particles.
[0020] [4] Other ingredients The precursor used in the present invention may contain, in addition to the components mentioned above, other components that are typically used in fuel cell separators. Other components include internal release agents such as stearic acid wax, amide wax, montanic acid wax, carnauba wax, and polyethylene wax, conductive assistants such as carbon black, and reinforcing materials such as carbon fiber. In particular, it is preferable to include carbon fiber from the viewpoint of further improving the strength of the recycled precursor and the separator obtained therefrom. From the viewpoint of improving reslurry of the precursor, the content of the other components is preferably 0.1 to 10 parts by mass, more preferably 0.1 to 5 parts by mass, and even more preferably 0.1 to 3 parts by mass, per 100 parts by mass of the graphite particles.
[0021] [5] Precursor production method The precursor used in the present invention can be obtained by dispersing a composition containing graphite particles, a particulate or fibrous water-insoluble resin used as required, and a water-soluble resin in water to prepare a precursor slurry, which is then molded by coating or casting, and then drying and removing the water. By uniformly dispersing the materials by wet kneading and molding them in this way, it is possible to suppress the generation of voids due to unfilled resin during heat compression molding, and to further improve gas impermeability.
[0022] Examples of the method for preparing the precursor by the coating method include a method in which the slurry is coated on a resin film such as a PET film, dried, and then peeled off from the resin film. The coating method is not particularly limited, and may be appropriately selected from known methods such as spin coating, dip coating, flow coating, inkjet coating, jet dispenser coating, spray coating, bar coating, gravure coating, roll coating, transfer printing, brush coating, blade coating, air knife coating, die coating, and screen printing.
[0023] An example of a method for producing a precursor by casting is to pour the slurry into a box-shaped mold, dry it, and then remove it from the mold. If a mold with a shape that reflects the irregularities of the separator is used in advance, a precursor with partially different thicknesses, which is difficult to produce by a coating method, can be produced. The material of the mold is not particularly limited, and may be appropriately selected from known materials such as a release-treated metal mold or a plastic mold made of silicone, fluororesin, or the like.
[0024] When a particulate or fibrous water-insoluble resin is used, the drying temperature for the slurry is not particularly limited as long as it is below the melting point or glass transition point of the resin, but is preferably below 100°C, more preferably from room temperature to 100°C, and even more preferably from 50 to 100°C.
[0025] The precursor used in the present invention may have any shape, and may be in the form of a sheet, plate, or the like. Furthermore, defective products generated during the production of a precursor by the above-mentioned method or scraps produced during processing can also be used as the precursor.
[0026] The form of the precursor used in the present invention is not particularly limited, but it is preferable that at least a part of it has a structure in which graphite particles and a particulate or fibrous water-insoluble resin used as necessary are fixed by a water-soluble resin.
[0027] [5] Method for producing regenerated precursor The precursor described above is mixed with an aqueous solvent to prepare a slurry, and the resulting slurry is dried to obtain a regenerated precursor. As the aqueous solvent, water or a mixed solvent of water and an organic solvent can be used, with water being preferred. The organic solvent is not particularly limited as long as it is soluble in water and does not dissolve the particulate or fibrous water-insoluble resin, and examples thereof include alcohols such as methanol and ethanol, polyhydric alcohols such as diethylene glycol and glycerin, etc. When an organic solvent is used, the amount of the organic solvent used is preferably less than 50% by mass in the aqueous solvent, more preferably less than 30% by mass, and even more preferably less than 15% by mass.
[0028] The precursor and the aqueous solvent may be mixed by any method, and the aqueous solvent may be added to the precursor, or the precursor may be added to the aqueous solvent. The amount of the aqueous solvent used is not particularly limited as long as it is capable of forming a slurry, but an amount that results in a solid content in the slurry of about 1 to 80 mass % is preferable, an amount that results in a solid content in the slurry of about 10 to 75 mass % is more preferable, and an amount that results in a solid content in the slurry of about 30 to 70 mass % is even more preferable. The precursor used in the present invention has a feature that the water-soluble resin redissolves when it comes into contact with water, and can be easily made into a slurry, so the slurry can be prepared at room temperature (about 15 to 30°C), but if necessary, it may be heated to a temperature that does not melt the particulate or fibrous water-insoluble resin. The temperature when heating can be, for example, about 50 to 80°C.
[0029] The method for obtaining the recycled precursor from the slurry involves molding the slurry using the coating method or casting method described above in the production of the precursor, and drying the slurry at the same temperature as in the production of the precursor. The regenerated precursor of the present invention can be formed into a sheet simply by drying and removing the aqueous solvent from the slurry, so that it is easy to form not only a simple flat sheet shape as in the conventional method, but also a sheet having an uneven shape with different thicknesses. The thickness of the regenerated precursor is not particularly limited, but is preferably from 100 μm to 1 mm, and more preferably from 200 to 800 μm.
[0030] In addition, the recycled precursor of the present invention is retained in shape by the dried water-soluble resin and has the strength to be handled in sheet form. However, when it comes into contact with water, the water-soluble resin dissolves again, so it can be made into a slurry multiple times, and defective products generated during precursor production and scraps during processing can be used without loss.
[0031] [6] Fuel cell separator The regenerated precursor obtained above can be heated and molded to produce a fuel cell separator. The molding method is not particularly limited, but compression molding is preferred. The temperature during compression molding is not particularly limited as long as it exceeds the melting point or glass transition point of the particulate or fibrous water-insoluble resin, but a mold temperature of 150 to 250°C is preferred. The molding pressure is preferably from 1 to 100 MPa, and more preferably from 1 to 60 MPa. The compression molding time is not particularly limited and can be appropriately set within a range from about 3 seconds to 1 hour.
[0032] In addition, when the recycled precursor contains a particulate or fibrous water-insoluble resin, the water-insoluble resin can be melted by heat compression molding to fill the voids and bond the graphite particles to obtain a separator of the desired shape. In this recycled precursor, the graphite particles are not coated with a water-insoluble resin in advance as in the past, and the formation of a resin layer on the separator surface during compression molding can be suppressed, so that a separator with low contact resistance and penetration resistance and high electrical conductivity and gas impermeability can be obtained. In particular, since the formation of a resin layer on the separator surface is suppressed, the step of removing the resin layer to improve electrical conductivity is unnecessary, and since the surface exposure rate of the graphite particles is increased, fine irregularities are formed, improving the adhesiveness of gaskets, etc., and further improving the releasability during hot compression molding.
[0033] Generally, a solid polymer electrolyte fuel cell is made up of a large number of unit cells arranged side by side, each unit cell being composed of a pair of electrodes sandwiching a solid polymer membrane and a pair of separators sandwiching these electrodes to form a gas supply and exhaust flow path. The fuel cell separator of the present invention can be used as some or all of these multiple separators. EXAMPLES
[0034] The present invention will be described in more detail below with reference to examples and comparative examples, but the present invention is not limited to the following examples.
[0035] [1] Preparation of recycled precursor sheet [Example 1-1] In terms of solid content ratio, 100 parts by mass of flake graphite (particle size 20 μm, same below), 7.1 parts by mass of polyacrylic acid (molecular weight 150,000, solid content concentration 25 mass% aqueous solution, same below) which is a water-soluble resin, 35.7 parts by mass of particulate phenolic resin (particle size 25 μm, molecular weight 10,000, same below) which is a particulate water-insoluble resin, and water as a solvent were mixed to prepare a slurry for producing a precursor sheet with a final solid content concentration of 50 mass%. The slurry was applied to a release-treated PET film using a bar coater, dried in a blower dryer at 80° C., and peeled off from the PET film to obtain a precursor sheet having a thickness of 480 μm. The obtained precursor sheet was mixed with water to prepare a slurry for producing a recycled precursor sheet with a final solid content of 50% by mass, and the slurry was applied to a release-treated PET film using a bar coater, dried in a blower dryer at 80°C, and peeled off from the PET film after drying to obtain a recycled precursor sheet. The thickness of the obtained recycled precursor sheet was 480 μm.
[0036] [Example 1-2] A recycled precursor sheet having a thickness of 480 μm was obtained in the same manner as in Example 1-1, except that the particulate water-insoluble resin was changed from particulate phenolic resin to powdered polypropylene (particle size 15 μm).
[0037] [Examples 1-3] A recycled precursor sheet having a thickness of 480 μm was obtained in the same manner as in Example 1-1, except that the amount of polyacrylic acid used was changed to 1.4 parts by mass, and the amount of particulate phenolic resin used was changed to 33.8 parts by mass.
[0038] [Examples 1-4] A recycled precursor sheet having a thickness of 480 μm was obtained in the same manner as in Example 1-1, except that the amount of polyacrylic acid used was changed to 15.4 parts by mass, and the amount of particulate phenolic resin used was changed to 38.5 parts by mass.
[0039] [Examples 1-5] A recycled precursor sheet having a thickness of 480 μm was obtained in the same manner as in Example 1-1, except that the amount of polyacrylic acid used was changed to 6.4 parts by mass, and the amount of particulate phenolic resin used was changed to 21.8 parts by mass.
[0040] [Examples 1-6] A recycled precursor sheet having a thickness of 480 μm was obtained in the same manner as in Example 1-1, except that the amount of polyacrylic acid used was changed to 8.3 parts by mass, and the amount of particulate phenolic resin used was changed to 58.3 parts by mass.
[0041] [Examples 1-7] A recycled precursor sheet having a thickness of 480 μm was obtained in the same manner as in Example 1-1, except that the amount of polyacrylic acid used was changed to 7.2 parts by mass, the amount of particulate phenolic resin used was changed to 36.1 parts by mass, and 1 part by mass of carbon fiber (φ7 μm, fiber length 6 mm) was further added.
[0042] [Comparative Example 1-1] A slurry was prepared in the same manner as in Example 1-1, except that the amount of particulate phenol resin used was changed to 33.3 parts by mass and polyacrylic acid was not added, but a precursor sheet could not be obtained.
[0043] [Comparative Example 1-2] A precursor sheet having a thickness of 480 μm obtained in the same manner as in Example 1-1 was pulverized in a mill mixer (YAMAZEN Corporation, YMH400-W) for 10 seconds x 5 times, and the pulverized powder was spread in a metal mold and pressed at 130°C and 30 MPa for 1 minute to obtain a regenerated precursor sheet.
[0044] The above examples and comparative examples are summarized in Table 1.
[0045] [Table 1]
[0046] The slurry dispersibility and reslurryability in Table 1 were evaluated by the following methods. [Slurry Dispersibility] The presence or absence of streaks or defects when the slurry for preparing the precursor sheet was applied to the PET film was visually confirmed, the thickness was measured at any six points, and the film was evaluated according to the following criteria. ◎: No streaks or defects, and the thickness variation of the obtained precursor sheet is less than 3% ◯: No streaks or defects, and the thickness variation of the obtained precursor sheet is 3% or more and less than 5% △: Streaks and defects cause unevenness, and the thickness variation of the obtained precursor sheet is 5% or more. ×: There are obvious streaks and defects and a precursor sheet cannot be obtained. [Reslurry] 30 g of the precursor sheet piece was added to 30 mL of water and stirred to re-form a slurry, and the presence or absence of streaks or defects upon application to the PET film was visually confirmed and evaluated according to the same criteria as for the dispersibility of the slurry described above. ◎: No streaks or defects, and the thickness variation of the obtained recycled precursor sheet is less than 3% ○: No streaks or defects, and the thickness variation of the obtained recycled precursor sheet is 3% or more and less than 5% △: Streaks and defects are observed, and the thickness variation of the obtained recycled precursor sheet is 5% or more. ×: There are obvious streaks and defects, and a recycled precursor sheet cannot be obtained.
[0047] [2] Fabrication of fuel cell separators [Example 2-1] The recycled precursor sheet obtained in Example 1-1 was compression molded using a flat mold at 180° C. and 60 MPa for 5 minutes to obtain a fuel cell separator. The thickness of the separator molded in a flat shape was 250 μm.
[0048] [Example 2-2] The recycled precursor sheet obtained in Example 1-2 was heated at 180°C for 10 minutes, and then compressed at 60 MPa using a flat mold while cooling for 20 minutes to obtain a fuel cell separator. The thickness of the separator molded in a flat shape was 250 μm.
[0049] [Examples 2-3 to 2-7, Comparative Example 2-1] A fuel cell separator was obtained in the same manner as in Example 2-1, except that the recycled precursor sheets were changed to those prepared in Examples 1-3 to 1-7 and Comparative Example 1-2.
[0050] The electrical conductivity of the resulting fuel cell separator was measured by the following method and evaluated according to the following criteria. The results are shown in Table 2. [Conductivity] A flat separator was molded and sandwiched between gold-plated copper electrodes with a side length of 2 cm. A pressure of 2.5 MPa was applied for 10 seconds, and then the pressure was reduced to 1.0 MPa. A current of 1 A / cm was applied between the gold-plated copper electrodes. 2 The interelectrode voltage was measured when a constant current of 1000 V was applied. The interelectrode voltage obtained was converted to resistance and used as the separator penetration resistance (unit: mΩ cm 2 ) and the conductivity was evaluated according to the following criteria. ◎: Piercing resistance is 8mΩ·cm 2 less than ○: Penetration resistance is 8mΩ·cm 2 More than 10mΩ cm 2 less than △: Penetration resistance is 10mΩ·cm 2 More than 15mΩ cm 2 less than ×: Penetration resistance is 15mΩ·cm 2 In the above case
[0051] [Table 2]
[0052] As shown in Table 2, the fuel cell separators produced in Examples 2-1 to 2-7 have good electrical conductivity, whereas the fuel cell separator produced in Comparative Example 2-1 has poor electrical conductivity.
Claims
1. A method for producing a precursor for a regenerated fuel cell separator, comprising the steps of: mixing a precursor for a fuel cell separator, which precursor contains graphite particles and a water-soluble resin, with an aqueous solvent to prepare a slurry; and drying the slurry.
2. 2. The method for producing a precursor for a regenerated fuel cell separator according to claim 1, wherein the precursor for a fuel cell separator contains a particulate or fibrous water-insoluble resin.
3. 3. A method for producing a fuel cell separator, comprising a step of molding a precursor for a regenerated fuel cell separator obtained by the method for producing a precursor for a regenerated fuel cell separator according to claim 1 or 2.
4. 4. The method for producing a fuel cell separator according to claim 3, wherein the molding step is a step of performing heat compression molding.
Citation Information
Patent Citations
Fuel cell separator, resin composition for it, and its manufacturing method
JP2007149466A
Thermoplastic resin composition and thermoplastic resin molded product
JP2007277475A
Dry particle-based electrochemical device and method for manufacturing the same
JP2007531245A
Porous electrode base material and method for manufacturing the same
JP2018055969A
Manufacturing method of separator for fuel cell
JP2006269313A